Identification of pavinane alkaloids in the genera Argemone and Eschscholzia by GC-MS - Cahlíková, Lucie; Kucera, Radim; Host'álková, Anna; Klimes, Jirí; Opletal, Lubomír (Natural product communications, 2012)
The genera Eschscholtzia and Argemone (Papaveraceae) represent a rich source of pavinane alkaloids, the identification of which in alkaloid extracts is generally problematic without standards. The alkaloid extracts of three Argemone and four Eschscholtzia species were analyzed using GC-MS. The alkaloids were identified based on comparison of their mass spectra with commercial libraries, with reported data in the literature and with spectra of reference compounds. A total of 23 alkaloids of six structural types (pavinane, protopine, benzylisoquinoline, benzophenanthridine, aporphine and protoberberine) were identified. The fragmentation pathway of pavinane alkaloids was used for their identification. O-Methylneocaryachine has been reported for the first time from a natural sources and the alkaloid pattern of Eschscholzia pulchella has been analyzed and described for the first time.
Keywords: Plant Leaves; Reference Standards; Argemone; Alkaloids; Benzylisoquinolines; plynová chromatografie s hmotnostně spektrometrickou detekcí; Gas Chromatography-Mass Spectrometry; alkaloidy; Eschscholzia; referenční standardy; benzylisochinoliny; listy rostlin